Implementasi Pengelolaan Wakaf MWCNU Kec. Kota Kediri Perspektif Undang-undang Nomor 41 Tahun 2004 tentang Wakaf - Abdullah Taufik; Muh. Alfian Arif (MAHAKIM Journal of Islamic Family Law, 2021)
The management of the concept of waqf is set in the MWC.NU district of Kediri City is quite simple, it means taking advantage of the status of MWC.NU is one of the Islamic organizations that act as Nazhir to maintain and prosper waqf assets in accordance with their allocation as outlined by the mandate of Law Numb. 41of The year 2004 concerning waqf. to handover of waqf assets from wakif candidates to the MWC NU management who will act as Nazhir, a verbal pledge is witnessed by religious leaders and community leaders, and then to`ll be registered with the KUA to get the Akte Ikrar Wakaf (AIW). The types of waqf assets are managed by MWC.NU Kota Kediri is immovable object waqf in the form of land and buildings which are allocated for worship and education. This type of research is field research using a descriptive qualitative approach, namely the object of research at the Majlis Representative Branch of NU as Nadzir (waqf manager) which will be studied based on the Law on Waqf Number 41 of 2004 and other literature related to the study of waqf.